Yaşam tarzına göre pazar bölümlendirme ve bireysel emeklilik sektörü üzerine bir uygulama - Uçar, Ergin (My University, 2006)
YAŞAM TARZINA GÖRE PAZAR BÖLÜMLENDİRME VE BİREYSEL EMEKLİLİK SEKTÖRÜ ÜZERİNE BİR UYGULAMA Teknolojinin ilerlemesi ve küreselleşmenin etkisi ile tüketiciler için seçenekler çoğalmış ve pazarlarda rekabet artmıştır. Bu rekabet ortamında yaşayabilmek için işletmelerin tüketicilerini çok iyi tanıması ve tüketicilerin ihtiyaç ve isteklerini en iyi şekilde karşılaması gerekmektedir. Bu nedenle günümüzde tüketici davranışlarının ve pazar bölümlendirmenin önemi artmıştır. Tüketici davranışları kavramı ise yaşam tarzının bir yansıması olarak karşımıza çıkmaktadır. Çalışmanın ilk bölümünde tüketici davranışı tanımlanmıştır. Tüketici davranışını pazarlamadaki yeri ve tüketici davranışını etkileyen etkenler incelenmiştir. İkinci bölümde ise bölümlendirme kavramı ve başlıca bölümlendirme çeşitleri anlatılmıştır. Çalışmanın uygulaması ise bireysel emeklilik sektörü üzerine yapılmıştır. Bireysel emeklilik ürünü; insanların gelecek ile ilgili beklentilerini, hayata bakışını, yaşamını sürdürmek istediği standardı yakından ilgilendirdiği için, uygulamayı bu sektörde yapmak oldukça anlamlı sonuçlar çıkartmaktadır.

MARKET SEGMENTATION WITH RESPECT TO LIFE STYLES and AN INVESTIGATION ON THE INDIVIDUAL PENSION SECTOR Due to tremendous technological advancements and the impacts of globalization, there has been an increase in available options that consumers can have and therefore rivalry in the market place has gained in strength. In order for companies to be able to survive in this rivalry-oriented market environment, it is crucial that companies get to know about consumers quite well and try to meet their needs and desires in the best way they possibly can. Hence, the importance of consumer behaviors and market segmentation has increased much. The very concept of “consumer behavior” happens to be a reflection of life styles. In the first part of the study, the concept of “consumer behaviors” has been defined. The meaning of consumer behaviors for marketing and the factors affecting consumer behaviors have been outlined and examined. In the second part of the study, market segmentation and basic segmentation types have been covered. The individual pension sector has been chosen as the object of focus for the implementation part of the study. As the products the individual retirement sector provides consumers with, have much to do with people’s expectations for the future and the levels of standards they’re willing to achieve for their lives, this very sector seems to have been quite sensible for the implementation of the study and many relatively meaningful results could be derived there from.
Keywords: Bireysel Emeklilik; Bölümlendirme; Tüketici Davranışı